Implementasi Sanksi Pidana Dan Etik Terhadap Oknum Anggota Kepolisian yang Melakukan Tindak Pidana Penyalahgunaan Narkotika - Fadly Devari; Tri Reni Novita (Albayan Journal of Islam and Muslim Societies, 2024)
This study examines the implementation of criminal sanctions and ethical codes against police officers involved in drug abuse. Law Number 35 of 2009 on Narcotics applies not only to the general public but also to members of the Indonesian National Police. The research focuses on the legal framework for ethical violations, law enforcement mechanisms by the Professional and Security Division (Bidpropam) of the North Sumatra Regional Police, and the challenges faced during enforcement. The study employs normative and empirical juridical approaches, supported by interviews with Aipda M. Ikhwan Hasibuan, a Bidpropam accreditor. Findings indicate that police officers proven to have abused narcotics remain subject to criminal proceedings despite disciplinary or ethical sanctions. Ethical hearings determine further measures, including dishonorable discharge if the imposed criminal sentence exceeds five years. Legal regulations governing these processes are stipulated in Law No. 35 of 2009, Law No. 2 of 2002 and 2003, Government Regulation No. 2 of 2003, and Police Regulation No. 7 of 2022. Obstacles in enforcement include the absence of alleged violators during proceedings and the lengthy duration of court trials. This study underscores that consistent law enforcement against police officers involved in narcotics abuse is essential to uphold the integrity of the police institution.